An In Vitro Comparative Study of the Adaptation and Sealing Ability of Two Carrier-Based Root Canal Obturators - Ahmed Alkahtani; Sara Al-Subait; Sukumaran Anil (The Scientific World Journal)
The study was done to assess the sealing ability and adaptation of RealSeal 1, and to compare it with Thermafil. 65 single-rooted extracted teeth were selected and root canal treatment was performed. Root canals were obturated with RealSeal 1 or Thermafil. A double chamber bacterial leakage model using E. faecalis was developed to assess the sealing ability. Samples were monitored daily for 60 days. After the bacterial leakage test, samples were embedded in resin and sectioned horizontally at 2 and 4 mm from the apical foramen. Specimens were examined under scanning electron microscope and digitally photographed. AutoCAD software was used to measure the gap between the canal surface and obturation material. Results were statistically analyzed using nonparametric Kaplan-Meier survival analysis for the bacterial leakage and t-test to compare the means of gap in RealSeal 1 and Thermafil at 2 and 4 mm. There was no significant difference between the RealSeal 1 and Thermafil with respect to leakage over time. At 2 mm and 4 mm, RealSeal 1 had significantly more gaps than Thermafil. From the observations it can be concluded that RealSeal 1 and Thermafil have comparable performance in terms of adaptation and sealing ability.